(untitled) (Research, Society and Development, 2020)
This article deals with discussions about the inclusion of People with Disabilities and about the concept of work as an educational principle linked in the context of Professional and Technological Education of the Federal context in Brazil. This way, we adopt the perspective of work as an educational principle in the formation of critical-reflective subjects in line with the guidelines set out for the constitution of the Federal Institutes of Education, Science and Technology. Thus, this discussion, an integral part of research in development at the master’s level, counts, for now, with part of the theoretical survey to the realization of the investigative enterprise, which is already characterized in a qualitative approach. This article finds theoretical support in books, scientific articles and legal provisions and points, to some extent, for final considerations, the relevance of problematizing inclusion, but also the access and permanence of People with Disabilities in the contexts Federal Institutes in the Professional and Technological Education (EPT) modality in Brazilian context.